The Politics of Difference in Transitional Justice: Genocide and the Construction of Victimhood at the Khmer Rouge Tribunal. Issue 3 (3rd July 2018) - Bernath, Julie
ABSTRACT: Although aiming to disrupt the othering that enables political violence and mass victimization, transitional justice processes – which are integral to international peacebuilding – may also (re)produce difference in intricate and possibly problematic ways. This article argues that as this dilemma is inherent to the politics of difference, it is crucial to consider how difference is constructed in transitional justice processes, and with what consequences, as this can feed into problematic processes of othering. This article focuses on the genocide charges at the Khmer Rouge tribunal in Cambodia, using transcripts of the legal proceedings and qualitative fieldwork conducted between 2013 and 2018.